Peningkatan Kecerdasan Spiritual Guru Melalui Kegiatan Morning Spiritual Gathering di Pesantren Darul Ilmi - Luthfi Anis Muadzin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to decrypt the implementation of Morning Spiritual Gathering (MSG) activities as an effort to increase the spiritual intelligence (SQ) of teachers at the Darul Ilmi Muhammadiyah Tarakan Islamic Boarding School. This study uses a qualitative approach with data collection techniques through observation, interviews, and documents. The results of the study show that the Morning Spiritual Gathering has a positive impact on improving the quality of teaching and interaction between teachers and students, as well as strengthening Islamic ukhuwah between teachers. In addition, this activity also increases teachers' sense of responsibility, patience, and empathy in teaching. MSG encourages teachers' self-reflection and creates a more Islamic environment, supporting the development of students' character. Some teachers proposed a variety of learning methods to increase participant engagement. Overall, MSG activities contribute to improving teachers' spiritual intelligence and a more conducive learning atmosphere in Islamic boarding schools.